2005
DOI: 10.2165/00139709-200524020-00003
|View full text |Cite
|
Sign up to set email alerts
|

Poisoning due to Pyrethroids

Abstract: The first pyrethroid pesticide, allethrin, was identified in 1949. Allethrin and other pyrethroids with a basic cyclopropane carboxylic ester structure are type I pyrethroids. The insecticidal activity of these synthetic pyrethroids was enhanced further by the addition of a cyano group to give alpha-cyano (type II) pyrethroids, such as cypermethrin. The finding of insecticidal activity in a group of phenylacetic 3-phenoxybenzyl esters, which lacked the cyclopropane ring but contained the alpha-cyano group (and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
428
0
22

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 531 publications
(453 citation statements)
references
References 82 publications
3
428
0
22
Order By: Relevance
“…Exposure to pyrethroid insecticides can induce neurobehavioral effects in rodents and other species, including humans 7,8,9,10 . Aspects of open field behavior and catalepsy 11,12 , conditioned behavior 12,13,14 , motor activity 15,16 , anxiety 11,17 and aggressive behavior 11 .…”
Section: Deltamethrin (Dtm [(S)-a-cyano-d-phenoxyben-mentioning
confidence: 99%
“…Exposure to pyrethroid insecticides can induce neurobehavioral effects in rodents and other species, including humans 7,8,9,10 . Aspects of open field behavior and catalepsy 11,12 , conditioned behavior 12,13,14 , motor activity 15,16 , anxiety 11,17 and aggressive behavior 11 .…”
Section: Deltamethrin (Dtm [(S)-a-cyano-d-phenoxyben-mentioning
confidence: 99%
“…Pyrethroids alter the gating characteristics of neuronal sodium channels, delaying their closure and resulting in a lowered action potential threshold and repetitive firing [9,10]. Although the mechanism of action of pyrethrins has not been as thoroughly investigated as pyrethroids, a review concluded that pyrethrins are also considered sodium channel toxins that possess a similar toxicodynamic effect as pyrethroids [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism of action of pyrethrins has not been as thoroughly investigated as pyrethroids, a review concluded that pyrethrins are also considered sodium channel toxins that possess a similar toxicodynamic effect as pyrethroids [11]. Pyrethrins and pyrethroids have a lower degree of mammalian and human toxicity than insects because insects have increased sodium channel sensitivity, a smaller body size, and lower body temperature [9].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that the mechanism of action differs in toxicity of type I and type II pyrethroids [22,24]. In humans, dermal exposure to permethrin can cause irritation, itching, and paresthesia, while ingestion may cause nausea, vomiting, sore throat, abdominal pain, coma, convulsions and death [25][26][27]. Studies have shown that dermal exposure of permethrin has caused irritation in rabbits, and ingestion of the product has caused transient signs in dogs, including tremors [18,28].…”
Section: Discussionmentioning
confidence: 99%